Traffic calming devices :application and its effectiveness - Nail, Frankie Anak (Universiti Malaysia Sarawak (UNIMAS), 2006)
Speeding problem in some area especially where there are high pedestrian flows mainly school children's and ederly people has becomes a major concern to the public. Many accidents reported which involves pedestrians at such area were caused by excessive speeding vehicles. To mitigate the situations, installation of traffic calming devices were implemented by the local government. Thus, the aims of this study were to find out the effectiveness of various type traffic calming devices installed at the roadway. Also, this research will gather all the relevant information on the standard design material used for the traffic calming devices. This sites were chosen for each type of traffic calming devices implementation is yellow rumble strips at Tabuan Jaya. speed hump at Jalan Song and speed table at Jalan Padungan. Spot speed studies were carried out at the selected sites to obtain the required data. Then, the normal and cumulative distribution curves were plotted based on the traffic data obtained. Further analyses by employing SPSS were carried out to find the relationship and the effectiveness of the devices. From the studies, it has found that yellow rumble strips at Tabuan Jaya to Samarahan reduce the average speed by 7.5 kph or 10.7%, the speed bump at Lorong Song 3 to BDC reduce the average speed by 6.8 kph or 14.1% and speed tables at Jalan Padungan reduce the average speed by 6.8 kph or 14.6%. From correlation analysis conducted, the entry speeds decreases very significantly as the width of traffic calming devices increases (R^2 ta 1.0). The effect of the height of the devices also highly significant at reducing the vehicle entry speed (R^2 = 0.9217). Potential recommendation for a better way or guidelines for traffic calming devices installation is also addressed or presented in this report.